Analysis of SIMRS Implementation in Supporting Management Decision Making at Bhayangkara Hospital Makassar (International Forum of Researchers and Lecturers, 2025)
Information systems are essential tools in supporting rational decision-making processes, as they provide the necessary data for analyzing problems and evaluating alternative solutions. Effective decision-making requires accurate, timely, and relevant information to optimize hospital management operations. In the healthcare sector, the Hospital Management Information (Sistem Informasi Manajemen Rumah Sakit/SIMRS) plays a strategic role in facilitating management decisions across multiple operational aspects. This study aimed to examine how SIMRS implementation supports management decision-making at Bhayangkara Hospital Makassar, focusing on six key aspects: performance, information, economy, control, efficiency, and service. The research applied a qualitative methodology involving in-depth interviews with four informants who were directly involved in SIMRS operations. The results indicate that SIMRS at Bhayangkara Hospital Makassar has been implemented effectively. From the performance perspective, it operates well and meets user requirements. Regarding information, SIMRS produces accurate data, although certain outputs require additional processing using SPSS for detailed analysis. In terms of economy, it demonstrates efficiency by integrating with supporting services such as BPJS bridging. The control aspect is well-managed, as each staff member has unique login credentials, ensuring secure access. SIMRS also meets efficiency criteria, as users can quickly learn and operate the application according to established guidelines. For the service aspect, SIMRS aligns with hospital needs, and future enhancements will focus on measuring application maturity through digital maturity assessments. In conclusion, SIMRS significantly supports hospital management decision-making at Bhayangkara Hospital Makassar. However, further development is recommended to enhance data visualization and streamline reporting, enabling more effective and timely managerial decisions.